VD_FINDINFO Arrêt / 2010 / 1034 vom 1. Juli 2010 - VD Tribunal cantonal (2010)
OBLIGATION D'ENTRETIEN, TRANSACTIONACCORD, REJET DE LA DEMANDE, SUBROGATION LÉGALE | 134 al. 3 CC, 276 al. 2 CC, 287 al. 1 CC, 315b al. 2 CC, 420 al. 2 CC, 489 CPC